Organ‐saving surgery for rectal cancer after neoadjuvant chemoradiation: Analysis of failures and long‐term results. Issue 2 (1st December 2019) - Cosimelli, Maurizio; Ursi, Pietro; Mancini, Raffaello; Pattaro, Giada; Perri, Pasquale; Parrino, Chiara; De Peppo, Valerio; Diodoro, Maria Grazia; Balla, Andrea; Grazi, Gian Luca
Abstract: Background: To analyze long‐term results and risk of relapse in the clinical TNM stages II and III, mid‐low rectal cancer patients (RC pts), treated with transanal local excision (LE) after major response to neoadjuvant chemoradiation (n‐CRT). Methods: Thirty‐two out of 345 extraperitoneal cT3–4 or N+ RC pts (9.3%) underwent LE. Inclusion criteria: extraperitoneal RC, adenocarcinoma, ECOG Performance Status ≤2. Pts with distant metastases were excluded. Results: All pts showed histologically clear margins of resection and 81.2% were restaged ypT0/mic/1. Nine out of 32 (28.1%) pts relapsed: 7 (21.8%) showed a local recurrence, of which 5 (15.6%) at the endorectal suture, 1 (3.1%) pelvic and 1 (3.1%) mesorectal. Two pts (6.2%) relapsed distantly. Among the pT0/1, 11.5% relapsed vs 100% of the pT2 and pT4 ones. The six pts relapsing locally or in the mesorectal fat underwent a salvage total mesorectal excision surgery. The old patient with pelvic recurrence relapsed after 108 months and underwent a re‐irradiation; the two pts with distant metastases were treated with chemotherapy followed by radical surgery. Conclusions: Presently combined approach seems a valid option in major responders, confirming its potential curative impact in the ypT0/mic/1 pts. A strict selection of pts is basic to obtain favourable results.